Histological, Immunohistological, and Clinical Features of Merkel Cell Carcinoma in Correlation to Merkel Cell Polyomavirus Status - T. Jaeger; J. Ring; C. Andres (Journal of Skin Cancer)
Merkel cell carcinoma is a rare, but highly malignant tumor of the skin with high rates of metastasis and poor survival. Its incidence rate rises and is currently about 0.6/100000/year. Clinical differential diagnoses include basal cell carcinoma, cyst, amelanotic melanoma, lymphoma and atypical fibroxanthoma. In this review article clinical, histopathological and immunhistochemical features of Merkel cell carcinoma are reported. In addition, the role of Merkel cell polyomavirus is discussed.